Relationship between access to information in social media and the substitution of technical/scientific knowledge (Research, Society and Development, 2021)
Algorithms are increasingly used to streamline the internet search and search process, however, while facilitating this process, they can also influence people's health. Thus, it is necessary an approach about how this tool can negatively influence the well-being condition of individuals. A research was carried out in health databases, using inclusion and selection criteria for the selection of scientific articles. It was clear that the study of fluctuations in internet search terms is no longer restricted to Marketing, because large technological conglomerates already use the behavior of searches to "indicate" content to users. This expansion of territory is useful in the indication of cycles of collective interest driven mainly by the behavior of influencers, who, together with companies, promote the commodification of health and can negatively impact those who consume information. The algorithms present in social media have a negative impact on the lives of internet users. Partnerships between digital influencers and pharmaceuticals pose a risk to the health of lay individuals, as it encourages the consumption of products without medical supervision. Therefore, it is necessary that there be the continuation of scientific productions that address the doubts of users with understandable language, and thus address their questions with well-based information.